Self-Awareness Analysis as an Indicator of Social-Emotional Competence in Elementary School Students - Anjarsari, Lia; Gunansyah, Ganes; Nasution, Nasution (IKIP PGRI Bojonegoro, 2025)
This study examines the role of self-awareness in the development of social-emotional competencies among primary school students. Self-awareness, as a key aspect of emotional intelligence, enables students to recognize and manage their emotions, understand their strengths and weaknesses, make decisions, express their thoughts, and evaluate their actions. The research was conducted at SDN Bogoarum 2, with 16 students from grades 5 and 6 as subjects. Data were collected using a self-awareness questionnaire based on Daniel Goleman’s theory, complemented by interviews with teachers. The results showed that 68.75% of students exhibited a high level of self-awareness, while the remaining 31.25% scored lower. The study found that self-awareness positively influenced emotional regulation, decision-making, and self-expression. However, areas such as making decisions and articulating thoughts needed further improvement. These findings underscore the importance of self-awareness in fostering emotional and social development in students, which is crucial for their academic success and interpersonal relationships.